2018
DOI: 10.7189/jogh.08.020409
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of associations between non-communicable diseases and socioeconomic status within low- and lower-middle-income countries

Abstract: BackgroundNon-communicable diseases (NCDs) are the leading cause of death globally. Eighty-two percent of premature NCD deaths occur within low- and lower middle-income countries (LLMICs). Research to date, largely drawn from high-income countries, suggests that disadvantaged and marginalized groups have a higher NCD burden, but there has been a dearth of research studying this relationship within LLMICs. The purpose of this systematic review is to map the literature on evidence from LLMICs on the socio-econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
130
2
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 85 publications
7
130
2
11
Order By: Relevance
“…Socioeconomic inequality is a factor that in itself leads to an increase in NCDs in low-income populations. Global analyses across countries suggest that living in a low-income country is associated with a marked risk of developing chronic diseases 4,5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Socioeconomic inequality is a factor that in itself leads to an increase in NCDs in low-income populations. Global analyses across countries suggest that living in a low-income country is associated with a marked risk of developing chronic diseases 4,5 .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, NCDs are also a major health problem, accounting for 75% of the causes of death and, although they affect individuals from all socioeconomic strata, those from vulnerable groups, such as the elderly and those with low levels of education and income, are hit the hardest 3 . Additionally, studies demonstrate a relationship between social determinants, poor socioeconomic conditions and poor health outcomes with greater susceptibility to develop NCDs and their comorbidities, in addition to higher mortality rates 2,4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Spain in 2010, found out that the prevalence of the advanced chronic disease in the elderly can reach 10.9% [7]. When the risk of developing non communicable diseases is evaluated, the socio-economic status of the country has a main role [8], putting the Latin American countries in the spotlight of the problem. By the year 2050, life expectancy in Brazil is estimated to be eighty years old [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, according to the data of the statistical center of Iran in 2017, household income per capita reduced with increased family size [33] which means parents with more children might be under greater economic pressure. These economic problems could have adverse effects on socioeconomic status which can lead to CVD development through psychosocial factors (anxiety and depression development), using unhealthier diet, smoking initiation, limiting leisure-time physical activity, poor access to health care and little knowledge about diseases [34][35][36].…”
Section: Discussionmentioning
confidence: 99%